The Impact of Climate Change on the Productivity of Nutmeg (Myristica fragrans Houtt.) in Kamal Village, West Kairatu District - E. Ririhena, Rhony; Y. Wattimena, Anna; F.S. Tuanaya, Amina (Agrikan Jurnal Agribisnis Perikanan, 2023)
The research conducted in the village of Kamal, West Kairatu District, aims to prove that climate change has occurred and the relationship between climate and nutmeg productivity. The plant survey research used a random sampling method, the strata were determined based on the number of productive nutmeg plants, 30 samples of nutmeg plants were taken from 15 farmers. The analysis carried out was an analysis of rainfall under extreme conditions using rainfall data for the last 30 years (1992-2021 period) as well as an analysis of the relationship between rainfall and nutmeg productivity using regression analysis which tested using the Program Minitab 21. The results of the study showed that there was a deviation from extreme rainfall in Kamal village, namely the very extreme EL Nino event which caused rainfall in Kamal village to be 992 mm from normal conditions. a very extreme La Nina event caused rainfall in Kamal Village to increase by 1197 mm. The impact of climate change on the productivity of nutmeg in Kamal village is very closely related, namely the higher the rainfall, the higher the productivity of nutmeg, as indicated by the accuracy value of R2 = 82.1%.